2015
DOI: 10.1016/j.jash.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, oxidative balance score, and hypertension among a racially diverse population

Abstract: Hypertension is a risk factor for several vascular diseases. Evidence suggests that oxidative stress (OS) plays a significant role in its pathophysiology. Human studies have shown inconsistent results, varying based on the OS biomarker and study population. In a racially diverse population, examine the association between: (1) blood pressure or hypertension and four markers of OS and (2) blood pressure or hypertension and oxidative balance score (OBS). Using data (n = 317) from the cross-sectional study on rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…The search strategy retrieved 965 records. Twenty-one original articles on OBS were selected [9,10,11,12,13,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. These OBSs presented differences regarding their composition and association with health outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy retrieved 965 records. Twenty-one original articles on OBS were selected [9,10,11,12,13,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30]. These OBSs presented differences regarding their composition and association with health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…The number of components of the OBSs varied considerably among the scores, ranging between three and 20 components. There were five OBSs containing 13 components [16,19,22,25,27], four OBSs with 14 components [11,18,24,26], two OBSs with 12 components [10,15], two OBSs with 15 components [13,28], and two OBSs with eight components [17,29]. The remaining OBSs presented either 20 components [12], 16 components [23], 11 components [20], seven components [30], six components [21], or three components [9].…”
Section: Resultsmentioning
confidence: 99%
“…However, some papers found that OBS was associated with oxidative stress biomarkers (F2-isoprostane, fluorescent oxidation products, and so on) and was predictor for incident, sporadic colorectal adenoma [ 9 , 33 ]. None of the adjusted associations between hypertension and oxidative stress markers (including mitochondrial DNA copy number) were statistically significant except OBS [ 6 ]. Labadie et al reported that SOD2 , CAT , and GSTP1 did not modify OBS even though OBS was associated risk of disease [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the home interview, we asked questions about the age, gender, education, marital status, income, life styles, and physical exercise information. Individuals were considered hypertensive if they met any of the following conditions: (1) had ever been told by a doctor or healthcare professional that he or she had hypertension, (2) self-reported prescribed antihypertensive medication use, or (3) diagnosed with systolic blood pressure (SBP) ≥140 mmHg and diastolic blood pressure (DBP) ≥90 mmHg [ 24 ].…”
Section: Methodsmentioning
confidence: 99%